Analisis Efisiensi Pemasaran Produk Olahan Ubi Jalar (Ipomoea Batatas) di Kecamatan Ngargoyoso Kabupaten Karanganyar - Azzamia Azizah Andaru; Rhina Uchyani Fajarningsih (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
The Micro, Small and Medium Enterprises (MSMEs) are the largest group of economic actors in Indonesia. Processed products based on sweet potatoes are a typical food of Ngargoyoso District. Marketing is a process that MSMEs as producers must go through to distribute products into the hands of consumers. Ngargoyoso District has good quality processed sweet potato products. MSMEs have demonstrated the ability to maintain the national economy during times of crisis and encourage economic growth after the crisis. The research aims to determine existing marketing channels and obstacles and efficient and effective marketing channels for MSMEs for processed sweet potato products in Ngargoyoso District, Karanganyar Regency. The data used are primary and secondary. The analysis method uses the Shepherd, Acharya, and Aggarwal methods and the marketing efficiency index methods. The analysis results show that there are three marketing channels, namely online, offline, or both. Non-digital and digital access are the most common obstacles MSMEs encounter for processed sweet potato products. The results from the three research data analysis methods used are greater than 1%, so it can be said that MSME’s marketing channels are efficient. It was found that the most efficient marketing channel was using offline marketing, producing the highest level of efficiency using the Shepherd method at 4.1%, the Marketing Efficiency Index method at 4.6%, and the same level of efficiency for the three marketing channels using the Acharya and Aggarwal method at 1%.